Academic achievement and personality traits of faculty members of Indian agricultural universities: their effect on teaching and research performance. Issue 1 (1st January 2017) - Ramesh, P.; Reddy, K. M.; Rao, R. V. S.; Dhandapani, A.; Siva, G. Samba; Ramakrishna, A.
ABSTRACT: Purpose: The present study was undertaken to assess academic achievement, teaching aptitude and research attitude of Indian agricultural universities' faculty, to predict indicators for successful teachers and researchers, and thereby enhancing the quality of higher agricultural education. Methodology: Five hundred faculty members were selected to elicit information on academic, teaching and research achievements. Teaching aptitude and attitude of faculty towards research were measured through standard psychometric tests. Correlation and regression analysis was carried out to establish the relationship among selected variables. Findings: Combination of academic achievement and teaching aptitude was a superior predictor for the teaching achievement compared to either of them alone. Similarly, research achievement of faculty was predicted better by the combination of academic achievement and research attitude . Practical Implications: The study showed the need for training faculty members in interpersonal relationships for effective teaching, and in research methodology and research processes for improving research attitude of faculty. Theoretical Implications: The expectancy-value model provides a useful framework to understand the role of attitude/aptitude in better prediction of research and teaching behavior . Originality/Value: The present study showed that teaching aptitude and research attitude be considered along with academic achievements for promoting quality teaching and research and hence the educational programmes.